Proceedings of 2nd International Multi-Disciplinary Conference Theme: Integrated Sciences and Technologies, IMDC-IST 2021, 7-9 2022
DOI: 10.4108/eai.7-9-2021.2315485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginger on Oxidative Stress Induced by Hydrogen Peroxide in Male Quail

Abstract: This study was conducted to investigate the effect of Ginger (Zingiber officinale) as an antioxidant and its ability to prevent the effect of H2O2-induced oxidative stress and its reflections on blood parameters and antioxidant status of male quail. 120 local male quail on 21 days aged were randomly distributed according to complete randomized design into 4 groups and reared until 56 days age as follows: Control group, H2O2 group (tap water with 0.5% H2O2), Ginger group (1000 mg ginger/kg ration), H2O2 with Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…On the contrary, the groups that were given ginger with H2O2 from the beginning of the experiment (G4) had a significantly higher PCV% than the H2O2 group at P≤0.05. That indicates an improvement in blood characteristics compared with the H2O2 group, due to the ginger antioxidant components, which help to strengthen the blood cell membranes and thus maintain the levels of these blood characteristics within normal levels (Abdul-Majeed and Abdul-Rahman, 2022;Ogbuewu et al, 2019).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…On the contrary, the groups that were given ginger with H2O2 from the beginning of the experiment (G4) had a significantly higher PCV% than the H2O2 group at P≤0.05. That indicates an improvement in blood characteristics compared with the H2O2 group, due to the ginger antioxidant components, which help to strengthen the blood cell membranes and thus maintain the levels of these blood characteristics within normal levels (Abdul-Majeed and Abdul-Rahman, 2022;Ogbuewu et al, 2019).…”
Section: Resultsmentioning
confidence: 92%
“…Murakami et al (2000) reported that ginger has antioxidant capabilities comparable to or greater than those of vitamin E or C when used in the same quantities. Also, Al-Khalaifah et al (2022) revealed that ginger protects oxidatively stressed cells, which can occur in many pathological conditions and experimentally by many chemicals, including hydrogen peroxide (Abdul-Majeed and Abdul-Rahman, 2022).…”
Section: Introductionmentioning
confidence: 99%